Li3NbO4 - síntese, caracterização e aplicabilidade como eletrólito sólido para baterias recarregáveis - AZEVÊDO, Micael Rocha de (2022)
Lithium-ion batteries (LIBs) have a wide range of applications due to the advantages associated with their high energy densities. They are currently used in portable electronics, electric vehicles (EVs), and renewable energy storage. Despite advantages, they face safety-related problems due to the use of liquid electrolytes that are toxic and flammable. These problems can be solved by replacing liquid electrolytes with inorganic oxide solid electrolytes (SEs), which have high thermal stability and are usually compatible with higher potential cathodic materials. In this work, we investigated Li3NbO4’s feasibility of as a solid electrolyte for LIBs, as it constitutes the basis for an important family of cathode candidates with rocksalt structure for LIBs, but at the same time having a bandgap greater than 3 eV, which is attractive for SEs. The presence of niobium in the material is also attractive since this is an abundant metal in Brazil, compared to other countries. The material was synthesized by solid-state reaction and characterized by X-ray diffraction, Raman spectroscopy and electrochemical impedance spectroscopy (EIS), and its conductivity was determined at different temperatures. The material does not undergo decomposition or phase transitions over the analyzed temperature range (300- 1150K), confirming the hypothesis that it would have good thermal stability. As for charge transport properties, although the absence of subphases increases conductivity by approximately one order of magnitude and decreases activation enthalpy by ~ 0,1 eV, o- Li3NbO4 still has low total conductivity at room temperature (σ < 5 × 10-13 S/cm) and high total activation enthalpy (Htot ≥ 0,88 eV) when compared to the most promising SEs. Based on Nyquist plot profiles, Li3NbO4’s conduction is primarily electronic. Therefore, this material is not viable for application as SE in the investigated temperature range (T ≤ 673 K) in the pristine state. This result is not surprising since most good SEs have low ionic conductivity in the pristine state, and modifications are required to make it a good ionic conductor. Therefore, to increase the conductivity of such ordered phase, partial replacement of Nb by aliovalent ions is proposed to promote the formation of charge carriers (vacancies or interstitials). Preliminary results indicate that the disordered phase, whose formation we observed in in-situ XRD measurements at temperatures in the range 900-1000 K, has higher ionic conductivity and is, therefore, more promising. Further investigations of both approaches (partial replacement and disorder) will be carried out soon.